A Theoretical Conception of the Value System of Criticism in Chinese Children’s Literature - Li, Lifang (SARE: Southeast Asian Review of English, 2018)
This paper focuses on the value system of children’s literature criticism in China. This is examined against the backdrop of the current imbalance between the gains made by Chinese children’s literature in terms of composition and publication and the lag in theoretical criticism as well as lack of clear evaluation criteria. In approaching children’s literature criticism as a set of theoretical categories and meaning systems relating to value evaluation, the paper considers the following issues: the value relationship between the critical subject and the critical object, children’s literature values, value standards, and the accompanying critical and theoretical approaches that play a key role in this relationship. While the paper proposes and addresses problems based primarily on the Chinese context, it also touches on value issues in global children’s literature. It therefore seeks to promote cross-cultural dialogue and exploration of universal issues relating to the value dimension of children’s literature